Analysis of Income Level and Welfare of Lada Farmer Household (Piper Nigrum L.) in Bantilang Village, Towuti Subdistrict, East Luwu Regency - Mais Ilsan; Farizah Dhaifina Amran (Agribusiness Journal, 2022)
East Luwu Regency is one of the largest pepper centers in South Sulawesi Province. This study aims to: (1) know the production pepper farming, (2) analyze farmers’ income from pepper farming, (3) analyze the household income of pepper farmers and (4) analyze the level of welfare of pepper farmer households in Bantilang Village, Towuti District, East Luwu Regency. This research was conducted in Bantilang Village, Towuti District, East Luwu Regency from July to August 2021. The sample is 42 pepper farmers. The data was analysed using descriptive quantitative method. The results showed that (1) the level of pepper production in Bantilang Village, Towuti District, East Luwu Regency was quite high, that is 938.39 Kg/Ha. The income of pepper farmers is Rp. 4,353,953/month with the R/C-Ratio of 4.39, (2) household income of pepper farmers is relatively high, where their incomes are genterated from pepper farming, other farming, outside farming and income of household members, with the average household income of pepper farmers is Rp. 13,544,548/month, (3) the welfare of farmer households is high, where as many as 41 farmers are included in the prosperous category (97.62%).